Princípio da legalidade em matéria tributária: aspectos relevantes - Amaral, Adelúcia Miranda do (2007)
The object of this study consists in the analysis of the aspects concerning to the principle of legality within the tributary matter. Therefore we initially argued about the positive rights juridical system, as far as an object of study of the Science of Law, to be pursued by the jurist during its interpretation process and its consequential making of juridical norms. By considering that the principle of legality is one of constitutional instruments to warrant taxpayers rights, we analyzed the concerning aspects within the Brazilian constitutional juridical system, emphasizing the tributary constitutional subsystem, as supported by crowned values under the Federal Constitution of 1988, whereas Democratic State of Law. We also analyzed the juridical texts reception phenomenon stated under the former ordainment s shields in light of the new Brazilian juridical order. In the face of the principle of legality we analyzed some concerning aspects of tributary duties, specially the homologated duty. To the end, the conclusions that were able to be drawn from the presented assertions are shown in a shortened manner